MEMAKNAI PENGALAMAN UMAT MUSLIM YANG BEKERJA DI LEMBAGA KATOLIK: Suatu Penelitian Fenomenologis - Simanullang, Gonti (UNIKA Santo Thomas, 2022)
It is common to find adherents of the Islamic faith working in Catholic institutions such as in St. Peter’s Diocesan Formation House, Faculty of Philosophy of St. Thomas Catholic University, the Alverna Capuchin Fraternity, and the Nagahuta Franciscan Formation House (RPF), Simalungun Regency. The former three Catholic institutions are located in Sinaksak, Tapian Dolok District, Simalungun Regency. Dozens of Muslims have worked in one of these Catholic institutions for between 4-30 years. By interviewing five of them about their experiences working in Catholic institutions, significant perceptions and experiences were obtained, namely: conducive workplace, tolerance, dialogue, friendship, religion, and hope. Coexistence between Muslims and Catholics departs from and is grounded in humanity or the same dignity of human beings